Elephants: The Elephantine Affair in Uttar Pradesh and Uttarakhand - Chauhan, A. (Centre for Asian Studies, University of Kelaniya, Sri Lanka, 2016)
The relationship between the man and animal has existed since human emergence. This peculiar bond is reflected in his lifestyle and culture. Human beings tamed animals, hunted them used them for recreation and transport and above all worshipped them. Some of the animals and birds have also been represented in various art forms created by the man. These include birds such as peacock and parrot, aquatic animals like fish and tortoise and animals like bull, horse, cow, tiger and animals. The elephant is also considered very sacred by the Hindus, Buddhists and Jains. The present paper shall focus on the prehistoric, historic and contemporary cultures in two of the northern states; Uttar Pradesh and Uttarakhand with reference to the elephant. They are found in abundance in both these states. It is one of the most majestic living beings on the earth. They are the largest mammals on the earth. It is of two main categories, the African elephant and the Asian elephant. The former is greater in size. This gigantic animal has immense strength. It is interesting to find that they have a role in socio-cultural life and its effects on the human philosophy and aesthetics. They have been the subject of sculptures, paintings, woodcarvings and other creative fields. In the past the elephant was also involved in games and sports activities. It has served as a means of transport since ages. It has been a war animal also. Man uses him for rides and hunting even today. The study is based on secondary sources from various disciplines like history, anthropology, arts, philosophy and literature.